2013
DOI: 10.1620/tjem.231.223
|View full text |Cite
|
Sign up to set email alerts
|

Aging Decreases the Strength of Suprahyoid Muscles Involved in Swallowing Movements

Abstract: Swallowing disorders are common in the elderly, and aging is a factor that affects swallowing function. The elevation of the hyoid bone is important for swallowing and is controlled by the suprahyoid muscles. The hyoid and laryngeal elevation allows the bolus to enter the esophagus. The suprahyoid muscles, therefore, play an important role in swallowing. The effects of aging on suprahyoid muscle strength are unclear. In this study, we analyzed the effects of aging on suprahyoid muscle strength by comparing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 25 publications
1
49
1
2
Order By: Relevance
“…Lowering of the larynx and hyoid is believed to result from age-related atrophy of the suprahyoid muscle fibers, reduced tension, and loosening of the ligaments 14. On the other hand, a previous study reported that when comparing jaw opening force in healthy individuals, the strength of the suprahyoid muscles was lower in those aged ≥70 years than in those aged <70 years 9. Greater jaw opening force leads to higher hyoid position at rest because when measuring jaw opening force, the muscles and joints are in a fixated position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowering of the larynx and hyoid is believed to result from age-related atrophy of the suprahyoid muscle fibers, reduced tension, and loosening of the ligaments 14. On the other hand, a previous study reported that when comparing jaw opening force in healthy individuals, the strength of the suprahyoid muscles was lower in those aged ≥70 years than in those aged <70 years 9. Greater jaw opening force leads to higher hyoid position at rest because when measuring jaw opening force, the muscles and joints are in a fixated position.…”
Section: Discussionmentioning
confidence: 99%
“…Jaw opening force is correlated with grip strength, which is an indicator of systemic muscle strength 8. As compared with healthy adults, healthy elderly individuals have significantly reduced jaw opening force 9. Moreover, reduced jaw opening force has been suggested to increase the risk of aspiration and pharyngeal residue 10.…”
Section: Introductionmentioning
confidence: 99%
“…The operation time is usually associated with the extent of tumor progression, and surgeons may become fatigued as the operation time lengthens. The strength of tissues, possibly including nerves, in elderly patients is thought to be lower than that of younger patients (Iida et al 2013). These results demonstrate that gentle and precise surgical maneuvers are absolutely essential to prevent RLNP.…”
Section: Discussionmentioning
confidence: 99%
“…Most skeletal muscles are weakened during aging; however, it is unclear whether aging-associated muscle weakness is programed, concerning initially affected muscles and progression. Relevant to OPMD, dysphagia, resulting from weakness of pharyngeal muscles, and eyelid ptosis, resulting from weakness of the levator palpebrae muscle, is highly common in the elderly (Salvi et al, 2006; Fea et al, 2013; Iida et al, 2013). In contrast to the otherwise healthy population, in OPMD, symptoms start at an earlier age and seem more severe, possibly due to faster progression.…”
Section: Why Specific Muscles Seem To Be More Affected Than Other Musmentioning
confidence: 99%